KAJIAN YURIDIS PENGELOLAAN KEUANGAN DAERAH BERDASARKAN PERATURAN PEMERINTAH NOMOR 12 TAHUN 2019 - Pondaag, Audi Helri; Kereh, Ollij Anneke; Friend Henry Anis (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This research was carried out with the aim of reviewing and analyzing regional financial management arrangements based on transparency and accountability and to analyze implementation as transparency and accountability in regional financial management in North Sulawesi. The method used in this research is a normative legal research method which uses a statutory and regulatory approach to examine regulations for transparency and accountability in regional financial management and empirical methods to determine implementation as transparency and accountability in regional financial management. The research results show that regulating transparency and accountability in regional financial management is very important for providing General Principles of Good Governance. The principles of transparency and accountability are regulated in Law No. 23 of 2014 concerning Regional Government which is further regulated in PP no. 12 of 2019 concerning Regional Financial Management. Based on the Principle of Transparency, it guarantees access or freedom for everyone to obtain information about the implementation of regional financial management. Accountability is one of the prerequisites for implementing the process of implementing good governance. Accountability is generally associated with the process of accountability for a series of services provided or that have been carried out. Accountability Refers to a person's responsibility to parties who have the right to ask for accountability, especially regarding regional financial management.